2021
DOI: 10.1108/jfmm-09-2020-0183
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the role of regulatory focus in apparel attribute prioritization

Abstract: PurposeThe purpose of this study is to utilize consumers' regulatory focus as a segmentation variable to understand how and why consumers shift their tendency to prioritize certain apparel attributes.Design/methodology/approachSix hypotheses are developed and then tested via two experiments. Self-administered online questionnaire is used to collect data from a total of 1,178 participants recruited via Amazon Mechanical Turk. The collected data is analyzed using series of Chi-square tests and ANOVAs.FindingsRes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…T. Huang, 2018). Hyun (2021) held that the presentation of promotional information on in-store or e-commerce platforms and the products corresponding to the promotion drive consumers’ buying behavior, especially in the festive environment, where consumers are more sensitive to product promotion information. Das et al (2020) argued that holiday promotions are usually carried out in the form of presenting high arousal stimuli (e.g., background music, background colors) to online consumers.…”
Section: Theoretical Background and Hypotheses Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…T. Huang, 2018). Hyun (2021) held that the presentation of promotional information on in-store or e-commerce platforms and the products corresponding to the promotion drive consumers’ buying behavior, especially in the festive environment, where consumers are more sensitive to product promotion information. Das et al (2020) argued that holiday promotions are usually carried out in the form of presenting high arousal stimuli (e.g., background music, background colors) to online consumers.…”
Section: Theoretical Background and Hypotheses Developmentmentioning
confidence: 99%
“…In the study on the influence of the content composition and slot location of online advertisements on the visual attention of online consumers, it is found that regardless of whether the text advertisement contains pictures or not, the attention people paid to advertisements with discount information is significantly higher than that on advertisements without discount information (Y. T. Huang, 2018). Hyun (2021) held that the presentation of promotional information on in-store or ecommerce platforms and the products corresponding to the promotion drive consumers' buying behavior, especially in the festive environment, where consumers are more sensitive to product promotion information. Das et al (2020) argued that holiday promotions are usually carried out in the form of presenting high arousal stimuli (e.g., background music, background colors) to online consumers.…”
Section: Cognition and Emotions Of Online Promotionmentioning
confidence: 99%